Computational and Experimental Studies of Flexible Fiber Flows in a Normal‐Stress‐Fixed Shear Cell. Issue 1 (22nd September 2018) - Guo, Y.; Buettner, K.; Lane, V.; Wassgren, C.; Ketterhagen, W.; Hancock, B.; Curtis, J.
Abstract : Flow properties of flexible fibers are poorly understood compared to those of rigid particles. In this study, a Schulze ring shear tester is used to measure the flow properties of fibers made of cut fishing wire and cut rubber cord, which have different levels of flexibility. For a comprehensive study, the discrete element method is employed to simulate flexible fiber flows. The simulations are validated by comparing with the experimental measurements. Studies show that an increase in fiber bending modulus leads to a reduction in the deformation and solid volume fraction, but it has no effect on the shear stress with the same normal stress. An increase in fiber‐fiber friction coefficient, below a critical value of 0.8, can augment the angle of internal friction. The contact stiffness, contact damping coefficient, and bond damping coefficient only have limited impact on the shear flow behavior in the ranges considered. © 2018 American Institute of Chemical Engineers AIChE J, 65: 64–74, 2019